Internal Needs Assessments: A Worthwhile Endeavor?. Issue 2 (17th February 2021) - Prescott, Carolyn; Walker, Mary Ann; Isgrigg, Daniel D.; Sample, Angela
Abstract: On May 1, 2020, the Needs Assessment Committee submitted their final report of findings and recommendations to the dean of the Oral Roberts University Library, Dr. Mark Roberts. The report represented the culmination of approximately six months of a broad-based investigation of the Library, including an internal examination of the Library and an external study of Library resources, services, and staff. This Needs Assessment was unique in that a team of Library faculty and staff conducted it. Internal members of an organization rarely perform needs assessments for many reasons, including inherent bias and the potential distrust of those not on the assessment team. Further complicating matters for the Needs Assessment team was the onset of the COVID-19 pandemic and ensuing shutdown of Oral Roberts University's (ORU) physical campus at the end of March 2020 during the period of data collection. Even before the campus shutdown created new challenges, the university administration and board of trustees mandated the significant revision of faculty promotion and appointment due by the end of February 2020. This mandate also posed some difficulties for the Needs Assessment team in managing the assessment workload and stress. This paper discusses some of the rationales for performing an internal Needs Assessment and the Needs Assessment team's process. The authors also describe how they navigated the tensions inherent in an internal assessment, the additional demands of a university mandate, and the COVID-19 pandemic impact. Finally, the authors present some of the Needs Assessment team's recommendations that the Library has already implemented and some proposals that have been postponed due to the pandemic's effects.